Aqueous zinc battery composite positive electrode, preparation method thereof and aqueous zinc battery
By electrochemically polymerizing conductive polymers on the positive electrode of the aqueous zinc battery, forming a composite positive electrode, using the adsorption effect of conductive polymers on anions, the problem of polyiodine ion diffusion is solved, the conductivity and stability of the battery are improved, and the high performance is achieved Specific capacity and good cycle stability.
Patent Information
- Application Number
- CN202411140054.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-19
- Publication Date
- 2025-01-03
AI Technical Summary
Polyiodine ions formed by existing water-based zinc batteries diffuse to the anode, resulting in increased battery self-discharge and reduced efficiency, and heteroatom doping technology increases technical risks and manufacturing costs.
The conductive polymer is deposited on the current collector of the positive electrode through electrochemical polymerization to form a composite positive electrode, and a strong interaction is achieved by the adsorption of conductive polymers on anions and inhibiting the diffusion of polyiodine ions.
The conductivity, stability and cycle stability of water-based zinc batteries are improved, manufacturing costs are reduced, and high specific capacity and good cycle stability are achieved.
Smart Images

Figure CN119252837A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to an aqueous zinc battery composite positive electrode and a preparation method thereof, and an aqueous zinc battery, and belongs to the field of secondary batteries. Background Art
[0002] With the development of the global economy, human demand for energy is still increasing. However, the environmental problems caused by the excessive exploitation and utilization of fossil energy such as coal, oil, and natural gas are becoming more and more serious. In order to ease the contradiction between energy demand and environmental problems, the development and utilization of clean renewable energy has become an important development direction. However, the volatility and intermittency of renewable energy make it impossible to directly provide a stable and continuous power supply, and a large-scale energy storage system is required for the transition. Due to its high safety, environmental protection, and low cost, aqueous secondary batteries have broad application prospects in the field of large-scale power storage. In aqueous secondary batteries, iodine media are transferred through I - and I 2 The redox reaction between the two can provide 211 mAh g -1 The theoretical capacity of iodine-containing aqueous secondary batteries shows great potential as electrode active materials, especially the aqueous zinc-iodine battery with zinc electrode (theoretical capacity up to 820 mAh g-1), which has gradually become a hot research topic in recent years due to its safety and abundant reserves. However, there are still some serious problems restricting its development and application, such as the formation of polyiodide ions (I 3 - ,I 5 - ) will diffuse and shuttle to the anode, causing problems such as increased battery self-discharge and reduced efficiency. In order to inhibit the diffusion of polyiodide ions, researchers have developed methods such as ion-selective membranes, new gel electrolytes and electrode modification. Among them, electrode modification fundamentally inhibits the diffusion of polyiodide ions by increasing the adsorption capacity of the electrode for polyiodide ions, showing greater application potential than ion-selective membranes and new gel electrolytes. At present, electrode modification mainly improves the adsorption capacity of carbon materials for polyiodide ions through heteroatom doping technology. However, heteroatom-doped carbon materials only improve the adsorption capacity of polyiodide ions by changing the surface polarity and increasing lattice defects, and the adsorption effect is still a weak interaction. Moreover, heteroatom doping technology generally needs to be achieved through high-temperature calcination, which inevitably increases technical risks and manufacturing costs. Summary of the invention
[0003] In order to solve the above-mentioned problems existing in the prior art, the present application provides an aqueous zinc battery composite positive electrode, in which a conductive polymer is deposited on the positive electrode collector by electrochemical polymerization to form a composite positive electrode. The electrochemical deposition method can improve the conductivity of the composite positive electrode.
[0004] This application adopts the following technical solutions:
[0005] According to one aspect of the present application, there is provided an aqueous zinc battery composite positive electrode, comprising a current collector and a conductive polymer;
[0006] The conductive polymer is deposited on the current collector.
[0007] The conductive polymer is at least one selected from polypyrrole and its derivatives, polythiophene and its derivatives, polyaniline and its derivatives.
[0008] Optionally, the conductive polymer has a porous structure;
[0009] Optionally, the pore structure is a continuous micro-nano porous structure;
[0010] The pore size range is 1-50 nm.
[0011] The pore structure of conductive polymers can provide more active sites for iodide ions.
[0012] Optionally, the current collector is selected from at least one of aluminum, graphite, graphene, carbon, carbon fiber, and platinum;
[0013] Preferably, the current collector is carbon;
[0014] Preferably, the carbon has a porous structure.
[0015] Compared with heteroatom-doped carbon materials, carbon materials containing positively charged groups (-HN + =) The adsorption of anions by the conductive polymer is achieved through electrostatic attraction, which is a strong interaction. Moreover, the preparation technology of the conductive polymer is simple and easy to mass produce.
[0016] According to the second aspect of the present application, a method for preparing the above-mentioned aqueous zinc battery composite positive electrode is provided, comprising the following steps:
[0017] The current collector is immersed in a solution containing a conductive polymer monomer and a dopant, and the composite positive electrode is obtained after electrochemical polymerization.
[0018] Optionally, the dopant is selected from at least one of sulfates, chlorates and sulfonates.
[0019] Optionally, the molar concentration of the conductive polymer monomer in the solution is 0.1 mol / L to 0.8 mol / L;
[0020] Preferably, the molar concentration of the conductive polymer monomer in the solution is 0.2 mol / L to 0.6 mol / L.
[0021] Optionally, the molar concentration of the dopant in the solution is 0.4 mol / L to 2.0 mol / L;
[0022] Preferably, the molar concentration of the dopant in the solution is 0.6 mol / L to 1.4 mol / L.
[0023] Optionally, the conditions for the current in the electrochemical polymerization include:
[0024] The current density is 1mA / cm 2 ~10mA / cm 2 ;
[0025] The application time is 5min to 60min;
[0026] Preferably, the current density is 4 mA / cm 2 ~6mA / cm 2 ;
[0027] The application time is 10 minutes to 30 minutes.
[0028] According to a third aspect of the present application, an aqueous zinc battery is provided.
[0029] A mild aqueous solution containing iodine can prevent the conductive polymer in the composite positive electrode material from inventing redox reactions and increase the conductivity of the conductive polymer to anions I 3- ,I 5- of the electrolyte, preventing it from blocking I 2- The conductive polymer is not easy to undergo redox reaction in the near-neutral iodine-containing electrolyte, which improves the stability of the conductive polymer structure and ensures the cycle stability of the battery.
[0030] The aqueous zinc battery comprises a composite positive electrode;
[0031] The composite positive electrode is selected from at least one of the aqueous zinc battery composite positive electrodes described in any one of the above or the aqueous zinc battery composite positive electrodes obtained by any one of the above preparation methods.
[0032] Optionally, the aqueous zinc battery further comprises a negative electrode and an electrolyte;
[0033] The negative electrode is selected from one of an iron sheet, a zinc sheet, and a magnesium sheet;
[0034] The electrolyte in the electrolyte is selected from at least one of ferrous iodide, zinc iodide, magnesium iodide, potassium iodide, hydrogen iodide, sodium iodide, zinc chloride, zinc nitrate, and zinc sulfate;
[0035] The concentration of the electrolyte is 0.50mol / L to 3.00mol / L;
[0036] Preferably, the concentration of the electrolyte is 0.1 mol / L to 2.50 mol / L.
[0037] The beneficial effects of this application include:
[0038] (1) The aqueous zinc battery composite positive electrode provided in this application has high conductivity and excellent stability.
[0039] (2) The aqueous zinc battery provided in this application has a high specific capacity.
[0040] (3) The aqueous zinc battery and battery capacitor provided in this application have good cycle stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] Figure 1 This is the SEM microscopic morphology of the conductive polymer in Example 6 of the present application, wherein a and b are the microscopic morphologies at different magnifications, respectively. DETAILED DESCRIPTION
[0042] The present application is described in detail below with reference to embodiments, but the present application is not limited to these embodiments.
[0043] Unless otherwise specified, the raw materials in the examples of this application were purchased through commercial channels.
[0044] The analysis method in the examples of this application is as follows:
[0045] The morphology was analyzed using a SU-8010 field emission scanning electron microscope.
[0046] Electrochemical analysis was performed using a WaveDriver 200 potentiostat from Pine, USA, and a CT-4008 battery tester from Shenzhen Newwell Electronics Co., Ltd.
[0047] Example 1
[0048] Prepare 0.4mol / L pyrrole and 1mol / L sulfuric acid aqueous solution, use 1cm×2cm carbon felt as positive electrode, 1cm×2cm platinum mesh as negative electrode, apply 10mA constant current for 20min to prepare polypyrrole / carbon felt electrode. Cut 1cm×2cm polypyrrole / carbon felt electrode as composite positive electrode of aqueous zinc battery, 1cm×2cm zinc sheet as negative electrode, 0.75mol / L zinc iodide aqueous solution as electrolyte and separator, and assemble aqueous zinc-iodine battery.
[0049] Example 2
[0050] Prepare 0.2mol / L pyrrole and 1mol / L sulfuric acid aqueous solution, use 1cm×2cm carbon felt as positive electrode, 1cm×2cm platinum mesh as negative electrode, apply 20mA constant current for 20min to prepare polypyrrole / carbon felt electrode. Cut 1cm×2cm polypyrrole / carbon felt electrode as composite positive electrode of aqueous zinc battery, 1cm×2cm zinc sheet as negative electrode, 0.75mol / L zinc chloride and 1.5mol / L potassium iodide as electrolyte and diaphragm, and assemble aqueous zinc battery.
[0051] Example 3
[0052] Prepare 0.4 mol / L pyrrole and 0.4 mol / L sodium p-toluenesulfonate aqueous solution, use 1 cm×2 cm carbon felt as positive electrode, 1 cm×2 cm platinum mesh as negative electrode, apply 25 mA constant current for 40 min to prepare polypyrrole / carbon felt electrode. Cut 1 cm×2 cm polypyrrole / carbon felt electrode as composite positive electrode of aqueous zinc battery, 1 cm×2 cm zinc sheet as negative electrode, 0.75 mol / L hydrogen iodide aqueous solution as electrolyte and separator, and assemble aqueous zinc battery.
[0053] Example 4
[0054] Prepare 0.4 mol / L pyrrole, 0.4 mol / L ferric chloride, 0.4 mol / L sodium dodecylbenzene sulfonate aqueous solution, use 1 cm×2 cm carbon felt as positive electrode, 1 cm×2 cm platinum mesh as negative electrode, apply 25 mA constant current for 40 min to prepare polypyrrole / carbon felt electrode. Cut 1 cm×2 cm polypyrrole / carbon felt electrode as composite positive electrode of aqueous zinc battery, 1 cm×2 cm zinc sheet as negative electrode, 0.75 mol / L zinc iodide aqueous solution as electrolyte and separator, and assemble aqueous zinc battery.
[0055] Example 5
[0056] Prepare 0.4 mol / L 3,4-ethylenedioxythiophene and 0.4 mol / L ferric p-toluenesulfonate aqueous solution, use 1 cm×2 cm carbon felt as positive electrode, 1 cm×2 cm platinum mesh as negative electrode, apply 25 mA constant current for 40 min to prepare polypyrrole / carbon felt electrode. Cut 1 cm×2 cm polypyrrole / carbon felt electrode as positive electrode, 1 cm×2 cm zinc sheet as negative electrode, 0.5 mol / L zinc chloride and 1.0 mol / L potassium iodide aqueous solution as electrolyte and separator, and assemble aqueous zinc battery.
[0057] Example 6
[0058] Prepare 0.4mol / L aniline and 1mol / L sulfuric acid aqueous solution, use 1cm×2cm carbon felt as positive electrode, 1cm×2cm platinum mesh as negative electrode, apply 20mA current for 20min to prepare polyaniline / carbon felt electrode. Cut 1cm×2cm polyaniline / carbon felt electrode as composite positive electrode of aqueous zinc battery, 1cm×2cm zinc sheet as negative electrode, 0.75mol / L zinc chloride and 1.5mol / L potassium iodide aqueous solution as electrolyte, and assemble aqueous zinc battery.
[0059] Example 7
[0060] Prepare 0.2mol / L aniline and 1mol / L sulfuric acid aqueous solution, use 1cm×2cm carbon felt as positive electrode, 1cm×2cm platinum mesh as negative electrode, apply 20mA current for 20min to prepare polyaniline / carbon felt electrode. Cut 1cm×2cm polyaniline / carbon felt electrode as composite positive electrode of aqueous zinc battery, 1cm×2cm zinc sheet as negative electrode, 0.5mol / L zinc chloride and 1.0mol / L potassium iodide aqueous solution as electrolyte, and assemble aqueous zinc battery.
[0061] Example 8
[0062] Prepare 0.6mol / L aniline and 1mol / L sulfuric acid aqueous solution, use 1cm×2cm carbon felt as positive electrode, 1cm×2cm platinum mesh as negative electrode, apply 20mA current for 20min to prepare polyaniline electrode. Assemble aqueous zinc battery with 1cm×2cm polyaniline electrode as positive electrode, 1cm×2cm zinc sheet as composite positive electrode of aqueous zinc battery, and 0.75mol / L zinc iodide aqueous solution as electrolyte.
[0063] Example 9
[0064] 0.4 mol aniline and 0.8 mol sulfuric acid were dispersed in water to prepare 1L reaction solution, 1cm×2cm carbon felt was used as positive electrode, 1cm×2cm platinum mesh was used as negative electrode, and 20mA current was applied for 20min to prepare polyaniline electrode. 1cm×2cm polyaniline electrode was cut as composite positive electrode of aqueous zinc battery, 1cm×2cm zinc sheet was used as negative electrode, and 0.75mol / L zinc iodide aqueous solution was used as electrolyte to assemble aqueous zinc battery.
[0065] Example 10
[0066] 0.4 mol aniline and 1 mol sulfuric acid were dispersed in water to prepare 1L reaction solution, 1cm×2cm carbon felt was used as positive electrode, 1cm×2cm platinum mesh was used as negative electrode, and 10mA current was applied for 20min to prepare polyaniline electrode. Aqueous zinc battery was assembled with 1cm×2cm polyaniline electrode as composite positive electrode of aqueous zinc battery, 1cm×2cm zinc sheet as negative electrode, and 0.75mol / L hydrogen iodide aqueous solution as electrolyte.
[0067] Embodiment 11
[0068] 0.4 mol aniline and 1 mol sulfuric acid were dispersed in water to prepare 1L reaction solution, 1cm×2cm carbon felt was used as positive electrode, 1cm×2cm platinum mesh was used as negative electrode, and 10mA current was applied for 20min to prepare polyaniline electrode. Aqueous zinc battery was assembled with 1cm×2cm polyaniline electrode as composite positive electrode of aqueous zinc battery, 1cm×2cm zinc sheet as negative electrode, and 0.5mol / L aqueous solution of zinc iodide as electrolyte.
[0069] Example 12
[0070] Prepare 0.4mol / L aniline and 1mol / L sulfuric acid aqueous solution, use 1cm×2cm carbon felt as positive electrode and 1cm×2cm platinum mesh as negative electrode, apply 20mA current for 20min, prepare polyaniline / carbon felt electrode, cut 1cm×2cm polyaniline electrode as composite positive electrode of aqueous zinc battery. Prepare activated carbon electrode by conventional method, that is, activated carbon: conductive carbon black: CMC+SBR is prepared into slurry according to 8:1:1 and coated on zinc foil surface, rolled, cut into 1cm×2cm activated carbon electrode as negative electrode. Assemble in the manner of positive electrode, diaphragm, and negative electrode and add 0.75mol / L zinc chloride and 1.5mol / L potassium iodide aqueous solution to assemble aqueous zinc battery capacitor.
[0071] Comparative Example 1
[0072] A zinc-iodine battery was assembled using a 1 cm×2 cm manganese dioxide electrode as the positive electrode, a 1 cm×2 cm zinc sheet as the negative electrode, and a 0.75 mol / L zinc iodide aqueous solution as the electrolyte.
[0073] Comparative Example 2
[0074] 1 mol aniline and 1 mol sulfuric acid were dispersed in water to prepare a solution, 1 cm×2 cm carbon felt was used as the positive electrode, 1 cm×2 cm platinum mesh was used as the negative electrode, and 10 mA current was applied for 20 min to prepare a polyaniline / carbon felt electrode. A zinc-iodine battery was assembled with a 1 cm×2 cm polyaniline / carbon felt electrode as the positive electrode, a 1 cm×2 cm zinc sheet as the negative electrode, and 0.75 mol / L zinc chloride and 1.5 mol / L potassium iodide aqueous solution as the electrolyte.
[0075] Morphological characterization
[0076] The SEM morphology of the conductive polymer prepared in the embodiment is characterized, and a typical example is Figure 1 As shown, Figure 1 The scanning electron microscope image of the polyaniline (PANI@CF) prepared in Example 6 shows that the surface of the polyaniline has a rich micro-nano porous structure.
[0077] Electrochemical performance test
[0078] The CV curve of the conductive polymer electrode was tested by three electrodes with a conductive polymer electrode as the working electrode, a platinum mesh as the counter electrode, and a 1.5 mol / L potassium iodide aqueous solution as the test solution. The voltage scanning range was -0.5 V to -0.2 V, and the scanning rate was 2 mV s -1 , 5mV s -1 , 10mV s -1 , 20mV s -1 , 50mV s -1 The constant current charge-discharge curve of the battery was tested with two electrodes, the current was 20 mA, the voltage range was 0-1.25 V, and the specific capacity (mAh g -1 ). The battery was charged and discharged at a constant current of 20 mA and a voltage range of 0 to 1.25 V to test the cycle performance and charge and discharge cycle life of the battery (capacity retention rate 80%). The test results are shown in Table 1.
[0079] Table 1 Examples 1 to 11, Comparative Examples 1 and 2 have the following performances:
[0080] Example <![CDATA[Specific capacity (mAh g -1 )]]> Cycle times Example 1 218 2000 Example 2 229 3200 Example 4 231 4300 Example 5 233 5900 Example 6 243 9000 Example 7 239 7600 Example 8 234 7500 Example 9 232 6700 Example 10 228 5900 Embodiment 11 237 5800 Example 12 216 10000 Comparative Example 1 168 500 Comparative Example 2 145 600
[0081] It can be seen from the table that the battery specific capacity and cycle charge and discharge times of Comparative Examples 1 and 2 are low (500-600 times). The aqueous zinc battery prepared in Example 1-11 not only has a specific capacity of up to 218-243 mAh g -1 The comparison ratio is significantly improved, and the number of cycle charge and discharge is significantly improved compared with the comparison ratio. For example, the number of cycle charge and discharge of the batteries of Example 6 and Example 12 is as high as 9000-10000 times.
[0082] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.
Claims
1. A composite positive electrode for an aqueous zinc battery, characterized in that: including a current collector and a conductive polymer; The conductive polymer is deposited on the current collector; The conductive polymer is at least one selected from polypyrrole and its derivatives, polythiophene and its derivatives, polyaniline and its derivatives.
2. The aqueous zinc battery composite positive electrode according to claim 1, characterized in that: The conductive polymer has a porous structure; Preferably, the pore structure is a continuous micro-nano porous structure; The pore size range is 1-50 nm.
3. The aqueous zinc battery composite positive electrode according to claim 1, characterized in that: The current collector is selected from at least one of aluminum, graphite, graphene, carbon, carbon fiber, and platinum; Preferably, the current collector is carbon; Preferably, the carbon has a porous structure.
4. The method for preparing the composite positive electrode of an aqueous zinc battery according to any one of claims 1 to 3, characterized in that: The following steps are involved: The current collector is immersed in a solution containing a conductive polymer monomer and a dopant, and the composite positive electrode is obtained after electrochemical polymerization.
5. The preparation method according to claim 4, characterized in that: The dopant is selected from at least one of sulfate, chlorate and sulfonate.
6. The preparation method according to claim 4, characterized in that: The molar concentration of the conductive polymer monomer in the solution is 0.1 mol / L to 0.8 mol / L; Preferably, the molar concentration of the conductive polymer monomer in the solution is 0.2 mol / L to 0.6 mol / L.
7. The preparation method according to claim 4, characterized in that: The molar concentration of the dopant in the solution is 0.4 mol / L to 2.0 mol / L; Preferably, the molar concentration of the dopant in the solution is 0.6 mol / L to 1.4 mol / L.
8. The preparation method according to claim 4, characterized in that: The conditions for current in electrochemical polymerization include: The current density is 1mA / cm 2 ~10mA / cm 2 ; The application time is 5min to 60min; Preferably, the current density is 4 mA / cm 2 ~6mA / cm 2 ; The application time is 10 minutes to 30 minutes.
9. An aqueous zinc battery, characterized in that: The aqueous zinc battery comprises a composite positive electrode; The composite positive electrode is selected from at least one of the aqueous zinc battery composite positive electrode according to any one of claims 1 to 3 or the aqueous zinc battery composite positive electrode obtained by the preparation method according to any one of claims 4 to 9.
10. The aqueous zinc battery according to claim 9, characterized in that: The aqueous zinc battery also includes a negative electrode and an electrolyte; The negative electrode is selected from one of an iron sheet, a zinc sheet, and a magnesium sheet; The electrolyte in the electrolyte is selected from at least one of ferrous iodide, zinc iodide, magnesium iodide, potassium iodide, hydrogen iodide, sodium iodide, zinc chloride, zinc nitrate, and zinc sulfate; The concentration of the electrolyte is 0.50mol / L to 3.00mol / L; Preferably, the concentration of the electrolyte is 0.1 mol / L to 2.50 mol / L.
Citation Information
Cited By
Positive electrode of zinc-iodine battery, preparation method of positive electrode and battery
CN119943839A
Carbon nitride / carbon felt electrode for all-vanadium redox flow battery and preparation method of carbon nitride / carbon felt electrode
CN120690864A